2010
DOI: 10.1007/s00198-009-1165-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GH-IGF-I excess and gonadal status on bone mineral density and body composition in patients with acromegaly

Abstract: Our data support that GH-IGF-I excess and eugonadism have great influence on BC modifications and that the anabolic effects of GH-IGF-I on bone are, at least in part, dependent on these alterations in body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Several reasons for these conflicting results can be highlighted, such as the small sample sizes in the previous studies, the lack of patient stratification and separate analysis (based on the gender, disease activity, and gonadal status) in some of these studies, and the measurement of the BMD at different skeletal sites (6,8,9,35,36). In the present study, the only differences (based on the DXA parameters) were higher BMDs and T-scores only in the LS of patients with active acromegaly, whereas gonadal status did not have a significant effect on the BMD (Z-score), consistent with our group's previously published results (24). When the HR-pQCT parameters were analyzed, the only significant difference between the patients with active vs controlled acromegaly was higher cortical densities in the distal tibias of the active group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several reasons for these conflicting results can be highlighted, such as the small sample sizes in the previous studies, the lack of patient stratification and separate analysis (based on the gender, disease activity, and gonadal status) in some of these studies, and the measurement of the BMD at different skeletal sites (6,8,9,35,36). In the present study, the only differences (based on the DXA parameters) were higher BMDs and T-scores only in the LS of patients with active acromegaly, whereas gonadal status did not have a significant effect on the BMD (Z-score), consistent with our group's previously published results (24). When the HR-pQCT parameters were analyzed, the only significant difference between the patients with active vs controlled acromegaly was higher cortical densities in the distal tibias of the active group.…”
Section: Discussionsupporting
confidence: 92%
“…Values of Z-scores ՅϪ2.0 were considered to be lower than the expected bone mass. The coefficient of variation for the BMD measurements in normal subjects at our institution is 1.5% in the LS and 2.3% in the femoral neck (24).…”
Section: Methodsmentioning
confidence: 82%
“…Several studies have shown that GH substitution/therapy effectively decreases total, and particularly visceral, fat in various populations, such as patients with adult-onset GH deficiency, Prader-Willi syndrome, or obesity [6,7,8]. However, data regarding the specific AT distribution, rather than total body fat, and associations with metabolic risk factors in patients with acromegaly are limited [9,10,11]. Recently, a new dual-energy X-ray absorptiometry (DXA) application for quantifying VAT in the android region of the body was developed [12].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to musculoskeletal tissues in acromegaly, the effects of excess GH and IGF-I on BMD are conflicting. Some studies have described increased BMD in patients with active acromegaly [8][9][10], though aging, sex and hypogonadism in such patients correlate with decreased BMD [8,11]. GH excess causes an increase in bone turnover markers, such as bone formation and resorption markers [12].…”
mentioning
confidence: 99%